Preventing deaths from complications of labour and delivery. (October 2016) - Buchmann, Eckhart J.; Stones, William; Thomas, Niranjan
Abstract : The process of labour and delivery remains an unnecessary and preventable cause of death of women and babies around the world. Although the rates of maternal and perinatal death are declining, there are large disparities between rich and poor countries, and sub-Saharan Africa has not seen the scale of decline as seen elsewhere. In many areas, maternity services remain sparse and under-equipped, with insufficient and poorly trained staff. Priorities for reducing the mortality burden are provision of safe caesarean section, prevention of sepsis and appropriate care of women in labour in line with the current best practices, appropriately and affordably delivered. A concern is that large-scale recourse to caesarean delivery has its own dangers and may present new dominant causes for maternal mortality. An area of current neglect is newborn care. However, innovative training methods and appropriate technologies offer opportunities for affordable and effective newborn resuscitation and follow-up management in low-income settings. Highlights: There are still large rich–poor global disparities in labour-related mortality rates. Better access to safe caesarean section carries great promise, with risks attached. Regular emergency obstetric drills are indispensable elements of in-service training. Low-resource services must prioritise functional maternity units to save lives. Training and practice innovations can reverse the current neglect of newborn care.